Continuing education on child development for primary healthcare professionals: a prospective before-and-after study - Amira Consuêlo Melo Figueiras; Rosana Fiorini Puccini; Edina Mariko Koga Silva (São Paulo Medical Journal)
CONTEXT AND OBJECTIVE: Children's developmental disorders are often identified late by healthcare professionals working in primary care. The aim of this study was to assess the impact of a continuing education program on child development, on the knowledge and practices of these professionals.DESIGN AND SETTING: Prospective single-cohort study (before-and-after study), conducted in the city of Belém, Pará , Brazil.METHODS: Two hundred and twenty-one professionals working in primary healthcare (82.2%) participated in a continuing education program on child development and were assessed before and after implementation of the program through tests on their knowledge of child development, consisting of 19 questions for physicians and 14 for nurses, and questionnaires on their professional practices.RESULTS: One to three years after the program, the mean number of correct answers in the tests had increased from 11.5 to 14.3 among physicians in the Healthy Family Program (Programa Família Saudável, PFS); 13.0 to 14.3 among physicians in Municipal Health Units (Unidades Municipais de Saúde, UMS); 8.3 to 10.0 among PFS nurses; and 7.8 to 9.4 among UMS nurses. In interviews with mothers attended by these professionals before the program, only 21.7% reported that they were asked about their children's development, 24.7% reported that the professional asked about or observed their children's development and 11.1% received advice on how to stimulate them. After the program, these percentages increased to 34.5%, 54.2% and 30.3%, respectively.CONCLUSIONS: Professionals who participated in the program showed improved performance regarding child development knowledge and practices.